Financial Planning with Multiple Objectives - Sealey, C. W. (Financial management, 1978)
Financial planning problems with multiple conflicting objectives have recived much attention in the finance literature. While goal programming is the solution method most often applied to such problems, its application may result in inefficient decisions. This paper discusses multiobjective linear programming and compares the two methods by using a numerical example.